2022
DOI: 10.3390/ijms24010027
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Wheat GATA Transcription Factor Genes Reveals Their Molecular Evolutionary Characteristics and Involvement in Salt and Drought Tolerance

Abstract: GATA transcription factor genes participate in plant growth, development, morphogenesis, and stress response. In this study, we carried out a comprehensive genome-wide analysis of wheat GATA transcription factor genes to reveal their molecular evolutionary characteristics and involvement in salt and drought tolerance. In total, 79 TaGATA genes containing a conserved GATA domain were identified in the wheat genome, which were classified into four subfamilies. Collinear analysis indicated that fragment duplicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Genes belonging to the GATA-gene family are involved in the activation of a series of genes related to the regulation of the response to changes in the photoperiod and additionally regulate the accumulation of chlorophyll [22]. Nevertheless, the regulatory function of these genes is affected by environmental changes, thus their expression indirectly changes under abiotic stresses, as was reported in recent studies [78,79]. In the present study, the expression of the VvGATA26-like gene showed no remarkable change between the stressed plants and the control plants, and only a slight up-regulation was observed in the stressed self-rooted plants of the Dichali cultivar.…”
Section: Discussionmentioning
confidence: 93%
“…Genes belonging to the GATA-gene family are involved in the activation of a series of genes related to the regulation of the response to changes in the photoperiod and additionally regulate the accumulation of chlorophyll [22]. Nevertheless, the regulatory function of these genes is affected by environmental changes, thus their expression indirectly changes under abiotic stresses, as was reported in recent studies [78,79]. In the present study, the expression of the VvGATA26-like gene showed no remarkable change between the stressed plants and the control plants, and only a slight up-regulation was observed in the stressed self-rooted plants of the Dichali cultivar.…”
Section: Discussionmentioning
confidence: 93%
“…An intriguing aspect is their potential involvement in the tissue‐specific expression of genes associated with abiotic stress networks. For instance, investigations have demonstrated tissue‐specific expression of GATA members in potato, particularly in roots, inflorescences, and shoots (Saidi et al, 2021 ), while in wheat, the emphasis has been on leaf‐specific expression (Du et al, 2022 ). Unfortunately, conducting in silico expression analysis was challenging due to the limited information available in the solArray Potato Microarray Database.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, there is more substantial evidence regarding the role of GATA proteins in abiotic stress tolerance mechanisms. Overexpression of TaGATA62 and TaGATA73 in wheat was shown to increase expression levels in response to drought and salt stresses (Du et al, 2022 ). Similarly, two GATA genes in chickpea, CaGATA5 and CaGATA21 , were found to be upregulated during drought (Niu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The GATA transcription factor is a structurally related zinc finger protein that is highly conserved from insects to vertebrates. 14 It recognizes the GATA motif, an important cis-acting element in the promoters and enhancers of numerous genes. These transcription factors regulate cell fate determination and differentiation in a wide range of tissues.…”
Section: Introductionmentioning
confidence: 99%